Proliferation and cell death in an experimental model of brain tissue heterotopia in the lung - Quemelo,Paulo Roberto Veiga (2010)
PURPOSE: To investigate the proliferation and neuronal death in brain tissue heterotopia in the lung in an experimental model during both fetal and neonatal periods. METHODS: Twenty four pregnant female Swiss mice were used to induce brain tissue heterotopia on the 15th gestational day. Briefly, the brain of one fetus of each dam was extracted, disaggregated and injected into the right hemithorax of siblings. Six of these fetuses with pulmonary brain tissue implantation (PBI) were collected on the 18th gestational day (group E18) and six other on the 8th postnatal day (group P8). Immunohistochemical staining for PCNA and Bcl2 were used to assess proliferation and cell death. RESULTS: PCNA Labelling Index (LI) in heterotopic brain tissue was greater in fetal than postnatal period (E18 > P8) (p<0.05) and the immunostaining with Bcl2 antibody did not show difference. CONCLUSION: Cell proliferation is maintained in brain tissue heterotopia, although apoptosis is also observed.